Reconstructing the extraordinary palaeoflood events during 3200-2800 a BP in the upper reaches of Hanjiang River Valley, China - Zha, Xiaochun; Huang, Chunchang; Pang, Jiangli; Zhou, Yali (Journal of geographical sciences, 2014)
Palaeoflood hydrology study is a leading subject in global change study. Through field investigation in the upper reaches of Hanjiang River, palaeoflood slackwater deposits （SWD） were found in the bedrock gorges of the Yunxi reach. The results of field observation, laboratory analysis including particle-size distribution and magnetic susceptibility, and com- parison with modern flood deposits, the SWD were identified as the most typical Holocene palaeoflood deposits of the Hanjiang River. By using stratig;aphic correlation and OSL dating method, the palaeoflood event was dated to be 3200-2800 a BP at the turn from the middle to late Holocene. According to the palaeoflood peak stage and hydraulic parameters, the peak discharges of the palaeoflood were reconstructed as 48,830-51,710 m3/s by using the slope-area method. At same time, the flood peak discharges of 1983, 2005 and 2010 severe floods were reconstructed with the same method and hydraulic parameters in the same cross section. The error between the reconstructed and gauged discharges was 1.99%-4.21%. This showed that the reconstructed palaeoflood peak discharges were reliable. The flood peak discharge-frequency relationship at 10,000-year time scale was established by a com- bination of the gauged flood, historical flood and palaeoflood hydrological data. These results are very important for hydraulic engineering and flood mitigation on the Hanjiang River.